A scientometric study on research characteristics and trends of amyloidosis involving the oral cavity - Wei Liu; Cheng Jiang; Xuemin Shen; Yunteng Wu; Jie Wei (Journal of Dental Sciences)
Background/purpose: Oral involvement often constitutes the first sign of amyloidosis as a life-threatening disease that can lead to multiple organ impairment. The purpose of this study was to analyze the scientometric characteristics and research trends of amyloidosis involving the oral cavity. Materials and methods: All the papers on oral involvement of amyloidosis were comprehensively retrieved from the Scopus database. The years of publication were divided into before 2015 and 2015–2024 in the analysis of research trends. Results: There were 2540 relevant papers on amyloidosis involving the oral cavity, with total citations of 73,896 and the h index of 119. The related disorders were light chain amyloidosis, transthyretin amyloidosis, amyloid A amyloidosis, heart/cardiac amyloidosis, cardiomyopathy, kidney amyloidosis, and multiple myeloma. The trend of drug aspect, e.g. prednisone, colchicine, corticosteroid, doxorubicin, and vincristine before 2015 has changed to monoclonal antibody, daratumumab, tafamidis, proteasome inhibitor, carfilzomib, ixazomib, patisiran, pomalidomide, diflunisal, and doxycycline. Besides, the trend of clinical aspect has changed to complication, quality of life, risk factor, diagnostic imaging, prospective study, and early diagnosis after 2015. Herein, we highlight the awareness of early diagnosis and improve the access to care for amyloidosis, since oral involvement frequently constitutes the first sign of this disease. Conclusion: This scientometric study elucidated the current scenario and research trends of amyloidosis, underpinning that stomatologists can play roles in providing early recognition and timely diagnosis of amyloidosis when it involved the oral cavity.